Comparative Investigation on Drying Efficiency of the Solar Dryer Using Black Limestone as the Absorber Plate Against the Stainless Steel Absorber Plate for Drying Copra (Journal of Pharmaceutical Negative Results, 2022)
Aim: The aim of this study is to compare the novel black limestone absorber plate with stainless steel absorber plate for its drying efficiency of coconut. Materials and Methods: The sample size for the groups were determined as 20 for each group, a total of 40 for the groups using a simple sample size calculator, with G power of 80% by keeping threshold 0.05, confidence interval 95% and enrollment ratio as 1. The control and experimental groups were chosen as comparative groups. A sample size of 20 was allotted to each group. Coconut samples placed on the stainless steel are taken as a control group and the coconut samples placed on black limestone are taken as the experimental group. Moisture content of these coconut samples were determined with the help of a hot air oven and a formula. Results: The findings reveal that the mean value for the reduction of moisture content for black limestone is 29.06%, while the mean value for the reduction of moisture content for stainless steel is 36.10% of coconut samples. The independent samples t-test found that both groups are statistically significant for the reduction of moisture content, with a p value of 0.030. Conclusion: The drying performance of black limestone and stainless steel absorber plates in terms of moisture content reduction was experimentally tested, and it was discovered that black limestone absorber plate has a lesser drying efficiency than stainless steel absorber plate.